Three children with lipoatrophy associated with human rapid-acting insulin analogues. - Yazdanyar, S.; Dolmer, B.S.; Strauss, G. (European Journal of Pediatric Dermatology, 2011)
This report describes the development of severe lipoatrophy in three children with type 1 diabetes mellitus treated with the human insulin analogue Aspart. The number of cases with this complication of insulin therapy decreased significantly after the introduction of human recombinant insulin. However, in the past few years an increasing number of case reports have been published demonstrating that this cutaneous side-effect is also seen in association with various highly purified human insulin analogues. Therefore clinicians must be aware that lipoatrophy may still occur, although seldom, in patients treated with the technologically advanced insulin preparations.